2017
DOI: 10.14207/ejsd.2017.v6n2p187
|View full text |Cite
|
Sign up to set email alerts
|

Benzene and 1, 3 Butadiene Concentration and Its Potential Health Impact in Chiang Mai, Thailand

Abstract: Air pollution is contamination of the outdoor or indoor environment by any physical, biological or chemical agent that modifies the natural characteristics of the atmosphere. Air pollution can cause long-term and short-term health effects. An emerging air pollution issue in Thailand is the air toxics problem resulting from transportation and industrial activities. Cancer risk of benzene at Chiang Mai City Hall was within 3.00x10 -6 -1.20x10 -6 and Yupparaj Wittayalai School was within 9.30x10 -6 -1.20x10 -5 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In addition, CD3E was found to be targeted by several chemical small molecules, such as 1,3-butadiene and benzene. It is reported that 1,3-butadiene and benzene exposure can increase lifetime risk of cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CD3E was found to be targeted by several chemical small molecules, such as 1,3-butadiene and benzene. It is reported that 1,3-butadiene and benzene exposure can increase lifetime risk of cancer (40).…”
Section: Discussionmentioning
confidence: 99%